2022
DOI: 10.3390/foods11213539
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Variations in Brown Rice Fertilised with Different Levels of Nitrogen

Abstract: Nitrogen is a necessary element for plant growth; therefore, it is important to study the influence of N fertilisers on crop metabolites. In this study, we investigate the variability of endogenous metabolites in brown rice fertilised with different amounts of nitrogen. We identified 489 metabolites in brown rice. Compared to non-nitrogen fertilised groups, there were 59 differentially activated metabolic pathways in the nitrogen-fertilised groups. Additionally, there were significantly differential secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…The nutrient content in leaves can indicate the plant growth status and habitat conditions. For example, nitrogen is an essential component of various key cellular molecules such as proteins, nucleic acids, and secondary metabolites, which are important for maintaining plant metabolism and growth [7]. Previous studies have shown a significant relationship between leaf nutrient content and gender.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient content in leaves can indicate the plant growth status and habitat conditions. For example, nitrogen is an essential component of various key cellular molecules such as proteins, nucleic acids, and secondary metabolites, which are important for maintaining plant metabolism and growth [7]. Previous studies have shown a significant relationship between leaf nutrient content and gender.…”
Section: Introductionmentioning
confidence: 99%